DEFORMATION OF THE SUDBURY STRUCTURE: PALEOMAGNETIC EVIDENCE FROM THE SUDBURY BRECCIA - Szabó E.; Halls H.C. (My University, 2006)
Paleomagnetic results from fine-grained samples of Sudbury breccia, collected from 28 sites around the northern half of the 1.85 Ga Sudbury Igneous Complex (SIC), reveal the existence of two major components of magnetization, A and B. A, carried by magnetite, was formed close to the time of the SIC and has a direction that is related to the dip of the norite unit within the different ranges of the SIC. Component B, mainly carried by pyrrhotite, is a younger, secondary magnetization of more problematical origin, in part related to heating during the 1.24 Ga Sudbury magmatic event. In the northwest part of the SIC, A is found in breccia clasts, intermediate norite, sublayer, Levack Gneiss and Matachewan diabase, indicating that it is due to baking by the SIC. Tilt-correcting the West range by 36°, the North range by 22° and the northern East range by 36°, about axes parallel to local strike of the norite, minimises the dispersion of the paleomagnetic data to give a pre-folding direction of 199.4°/78.8°. The paleomagnetic data are similar to those obtained by Morris [Morris, W.A., 1984. Paleomagnetic constraints on the magmatic, tectonic, and metamorphic history of the Sudbury basin region. In: Pye, E.G., Naldrett, A.J., Giblin, P.E., (Eds.), The Geology and Ore Deposits of the Sudbury Structure, Special vol. 1. Ontario Geological Survey, pp. 411-427] on the SIC, suggesting for the first time that the SIC and the surrounding basement were deformed (probably during the 1.9-1.7 Ga Penokean Orogen) as a single unit. The un-folding of the paleomagnetic directions indicates that SIC limbs were already inclined, a result of the original intrusion configuration, or a syn-folding remanence. It is possible that the SIC was originally flatter if the distribution of paleomagnetic directions is the result of flexural flow folding. This explanation could also produce a similar distribution of paleomagnetic directions across the basin, but cannot be quantified due to the lack of measurable fold-related strain in breccia and SIC units around the northern half of the basin. © 2006 Elsevier B.V. All rights reserved.
Keywords: DEFORMATION; PALEOMAGNETISM; ROCK MAGNETISM; SUDBURY BRECCIA; SUDBURY STRUCTURE